Environmental, social and governance disclosure’s impacts on earnings management: Family versus non-family firms - Borralho, J.; Hernández-Linares, R.; Gallardo-Vázquez, D.; Paiva, I. (Journal of Cleaner Production, 2022)
Firms may strategically disclose corporate social responsibility (CSR) activities to compensate for their earnings management practices and, in this way, deflect stakeholders’ attention from non-standard reporting procedures. However, CSR dimensions can contribute differently to these practices, and these impacts may be affected by specific business contexts. This study investigated how each component of environmental, social and governance (ESG) disclosure individually affects earnings management in family versus non-family firms. The analysis used data from 2009 to 2018 on listed companies in France and Spain as these code law countries both have concentrated ownership. The results show that not all ESG dimensions are equally important for reducing earnings management and that the relationship between ESG disclosure and earnings management is affected by firms’ family or non-family status. The findings contribute to resolving the debate generated by inconsistent results reported regarding the relationship between disclosure of CSR activities and earnings management.